The use and abuse of police powers and extrajudicial killings in Nigeria - Igbo, Emmanuel (African journal of criminology and justice studies, 2017)
The paper examines the use and abuse of police powers in Nigeria, with emphasis on extrajudicial killing. It argues that extrajudicial killing is the most serious abuse of power and violation of victims’ rights to life and fair hearing. Using four typical case studies of live events from Nigerian newspapers, the paper shows that the police in Nigeria not only adopt the doctrine of maximum force in crime control, they often kill suspects and non-suspects at the flimsiest excuse because of an institutionalized culture of impunity. This culture of impunity is derived largely from Government’s authorization of a policy of shoot-to-kill, when in confrontation with armed robbers and other dangerous criminals.